Factors Influencing Intention To Use E-Government Services Among Iran Citizens - Salehi, Farhang (2012)
This study is part of a research effort which is trying to build up a holistic estimation structure for e-government systems. The major goal is to consider the citizen\'s perception in estimating e-government services and presenting a set of estimating factors which affect the citizens\' operations of electronic government services in Iran.